2012
DOI: 10.1016/j.molcel.2012.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Degradation of RNA Precursors by the Exosome in Wild-Type Cells

Abstract: Summary The exosome is a complex involved in the maturation of rRNA and sn-snoRNA, the degradation of short lived non-coding RNAs and in the quality control of RNAs produced in mutants. It contains two catalytic subunits, Rrp6p and Dis3p, whose specific functions are not fully understood. We analyzed the transcriptome of combinations of Rrp6p and Dis3p catalytic mutants by high-resolution tiling arrays. We show that Dis3p and Rrp6p have both overlapping and specific roles in degrading distinct classes of subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
273
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(292 citation statements)
references
References 59 publications
18
273
0
1
Order By: Relevance
“…tRNA Turnover and Cleavage tRNAs are stable with half-lives estimated to be from 9 hr to up to days (Anderson et al 1998;Phizicky and Hopper 2010;Gudipati et al 2012). So it is surprising that two separate pathways for tRNA turnover have been discovered (reviewed in Phizicky and Hopper 2010;Maraia and Lamichhane 2011;Parker 2012;Wolin et al 2012).…”
Section: Removal Of 59 Leader and 39 Trailer Sequences From Pre-trnasmentioning
confidence: 99%
See 1 more Smart Citation
“…tRNA Turnover and Cleavage tRNAs are stable with half-lives estimated to be from 9 hr to up to days (Anderson et al 1998;Phizicky and Hopper 2010;Gudipati et al 2012). So it is surprising that two separate pathways for tRNA turnover have been discovered (reviewed in Phizicky and Hopper 2010;Maraia and Lamichhane 2011;Parker 2012;Wolin et al 2012).…”
Section: Removal Of 59 Leader and 39 Trailer Sequences From Pre-trnasmentioning
confidence: 99%
“…Thus, this 39 to 59 turnover machinery likely serves as a quality control pathway that monitors both appropriate tRNA nuclear modification as well as 39 end maturation. Recent genome-wide studies indicate that as much as 50% of pre-tRNAs may be rapidly degraded by the exosome (Gudipati et al 2012). …”
Section: -59 Exonucleolytic Degradation By the Nuclear Exosomementioning
confidence: 99%
“…Hence, they are restrained at the transcription site or the proximity of the nuclear pore, and eventually degraded in the nucleus (Jackson et al, 2000). Moreover, recent studies focusing on exosome targets in transcriptome revealed that massive amounts of RNA precursors are degraded before they enter functional pathways in Saccharomyces cerevisiae (Gudipati et al, 2012;Schneider et al, 2012). All of these observations announced the presence of extensive nuclear RNA degradation in eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, both mRNAs and noncoding RNAs are subjected to quality control systems that eliminate incorrectly processed transcripts or misassembled ribonucleoprotein particles (Houseley and Tollervey 2009;Wolin et al 2012). A significant proportion of transcripts are degraded by such "RNA surveillance" processes, even in normally growing, healthy cells (Gudipati et al 2012). Finally, low level antisense and inter-genic transcription generates a large number of noncoding RNAs, many of which are subjected to rapid degradation (Wyers et al 2005).…”
Section: Introductionmentioning
confidence: 99%